Synthesis of Tellurium Nanoparticles Using Moringa oleifera Extract, and Their Antibacterial and Antibiofilm Effects against Bacterial Pathogens - Bo Ao; Honglin Jiang; Xuan Cai; Decheng Liu; Junming Tu; Xiaoshan Shi; Yanxiang Wang; Fei He; Jing Lv; Jingjing Li; Yuanliang Hu; Xian Xia; et al. (Microorganisms)
Today, pathogenic microorganisms are increasingly developing resistance to conventional drugs, necessitating the exploration of alternative strategies. In addressing this challenge, nano-based antibacterial agents offer a promising avenue of research. In the present study, we used an extract of Moringa oleifera, a widely recognized edible and medicinal plant, to synthesize biogenetic tellurium nanoparticles (Bio-TeNPs). Transmission electron microscopy, scanning electron microscopy, and dynamic light scattering analyses revealed that the obtained Bio-TeNPs had diameters between 20 and 50 nm, and zeta potential values of 23.7 ± 3.3 mV. Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy revealed that the Bio-TeNPs consisted primarily of Te(0), along with some organic constituents. Remarkably, these Bio-TeNPs exhibited potent antibacterial activity against a spectrum of pathogens, including Escherichia coli, Klebsiella pneumoniae, Shigella dysenteriae, Salmonella typhimurium, Streptococcus pneumoniae, and Streptococcus agalactiae. In addition, findings from growth curve experiments, live/dead cell staining, and scanning electron microscopy observations of cell morphology demonstrated that Bio-TeNPs at a concentration of 0.07 mg/mL effectively disrupted E. coli and K. pneumoniae cells, leading to cell rupture or shrinkage. The biofilm inhibition rates of 0.7 mg/mL Bio-TeNPs against E. coli and K. pneumoniae reached 92% and 90%, respectively. In addition, 7 mg/mL Bio-TeNPs effectively eradicated E. coli from the surfaces of glass slides, with a 100% clearance rate. These outcomes underscore the exceptional antibacterial efficacy of Bio-TeNPs and highlight their potential as promising nanomaterials for combating bacterial infections.